Culture conditions for equine bone marrow mesenchymal stem cells and expression of key transcription factors during their differentiation into osteoblasts. - Glynn, Elizabeth R.; Londono, Alfredo Sanchez.; Zinn, Steven A.; Hoagland, Thomas A.; Govoni, Kristen E. (2016)
Background: The use of equine bone marrow mesenchymal stem cells (BMSC) is a novel method to improve fracture healing in horses. However, additional research is needed to identify optimal culture conditions and to determine the mechanisms involved in regulating BMSC differentiation into osteoblasts. The objectives of the experiments were to determine: 1) if autologous or commercial serum is better for proliferation and differentiation of equine BMSC into osteoblasts, and 2) the expression of key transcription factors during the differentiation of equine BMSC into osteoblasts. Equine BMSC were isolated from the sterna of 3 horses, treated with purchased fetal bovine serum (FBS) or autologous horse serum (HS), and cell proliferation determined. To induce osteoblast differentiation, cells were incubated with L-ascorbic acid-2-phosphate and glycerol-2-phosphate in the presence or absence of human bone morphogenetic protein2 (BMP2), dexamethasone (DEX), or combination of the two. Alkaline phosphatase (ALP) activity, a marker of osteoblast differentiation, was determined by ELISA. Total RNA was isolated from differentiating BMSC between d 0 to 18 to determine expression of runt-related transcription factor2 (Runx2), osterix (Osx), and T-box3 (Tbx3). Data were analyzed by ANOVA.; Keywords: Bone marrow mesenchymal stem cells, Cell culture, Equine, Osteoblasts, Transcription factors.; Springer Open.